2020
DOI: 10.3390/pharmaceutics13010041
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Contribution of Chitosan Surface-Modified Nanoliposomes Combined with Colistin against Sensitive and Colistin-Resistant Clinical Pseudomonas aeruginosa

Abstract: Colistin is a re-emergent antibiotic peptide used as a last resort in clinical practice to overcome multi-drug resistant (MDR) Gram-negative bacterial infections. Unfortunately, the dissemination of colistin-resistant strains has increased in recent years and is considered a public health problem worldwide. Strategies to reduce resistance to antibiotics such as nanotechnology have been applied successfully. In this work, colistin was characterized physicochemically by surface tension measurements. Subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Dicloxacillin, commonly used in skin infections, demonstrated improved activity of non-coated liposomes; however, the activity of coated liposomes was retained compared to dicloxacillin in solution [ 79 ]. Chitosan-coated liposomes have also demonstrated promising antimicrobial effects in colistin-resistant Pseudomonas aeruginosa [ 80 ]. Sacco and colleagues evaluated a physical chitosan hydrogel against S. epidermidis and revealed promising antimicrobial activity [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dicloxacillin, commonly used in skin infections, demonstrated improved activity of non-coated liposomes; however, the activity of coated liposomes was retained compared to dicloxacillin in solution [ 79 ]. Chitosan-coated liposomes have also demonstrated promising antimicrobial effects in colistin-resistant Pseudomonas aeruginosa [ 80 ]. Sacco and colleagues evaluated a physical chitosan hydrogel against S. epidermidis and revealed promising antimicrobial activity [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan has been used by Laverde-Rojas et al to coat colistin-loaded liposomes. These liposomes were 4-fold more effective against clinical isolates of P. aeruginosa, while being equally active against multidrug-resistant strains compared to a colistin solution [47]. Aboumanei et al executed in vivo biodistribution studies of thigh muscle Escherichia coli infection-bearing mice with chitosan-coated liposomes encapsulating colistin and showed that upon oral administration, the bioavailability of colistin in the blood was improved more than 5-fold for chitosan-coated liposomes compared to a colistin solution.…”
Section: Liposomesmentioning
confidence: 99%
“…One of these modified cellulose biopolymers is carboxymethylcellulose (CMC), which is a water-soluble anionic polyelectrolyte widely recognized for its excellent flocculating capacity on various industrial contaminants, primarily of cationic nature [ 13 ]. In contrast, chitosan also belongs to the polysaccharide-type biopolymer family and is primarily extracted from the exoskeleton of crustaceans through the alkaline deacetylation of chitin [ 14 ]. It is the second-most abundant natural organic source on Earth after cellulose biopolymers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%